1993
DOI: 10.1165/ajrcmb/9.5.496
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Causes a Protein Kinase C-independent Increase of Paracellular Permeability in an In Vitro Epithelial Model

Abstract: To evaluate the response of an epithelial barrier to a moderate but sustained oxidative stress, we cultured monolayers of Madin Darby canine kidney cells on microporous filters and exposed them to the hypoxanthine-xanthine oxidase (HX-XO) reaction. The transepithelial permeability coefficient for mannitol (Pm) was assessed as a marker of paracellular permeability. When the oxidative stress was limited in intensity and duration (production of 10 nmol/ml/min O2- with generation of 467 +/- 30 nmol/ml H2O2 over 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…The current study was the first to investigate the recovery of barrier function after oxidant injury in AEC. Other recovery studies after oxidant injury (Welsh et al, 1985;Rochat et al, 1993;Meyer et al, 2001) and after surfactant treatment (Pasternak and Miller, 1996) have been performed on MDCK cell monolayers. The severity of the insult resulting from increased exposure time (Welsh et al, 1985;Rochat et al, 1993;Pasternak and Miller, 1996;Meyer et al, 2001) and the agent of injury (Pasternak and Miller, 1996) were found to be important factors in the ability of the BF to recover.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The current study was the first to investigate the recovery of barrier function after oxidant injury in AEC. Other recovery studies after oxidant injury (Welsh et al, 1985;Rochat et al, 1993;Meyer et al, 2001) and after surfactant treatment (Pasternak and Miller, 1996) have been performed on MDCK cell monolayers. The severity of the insult resulting from increased exposure time (Welsh et al, 1985;Rochat et al, 1993;Pasternak and Miller, 1996;Meyer et al, 2001) and the agent of injury (Pasternak and Miller, 1996) were found to be important factors in the ability of the BF to recover.…”
Section: Discussionmentioning
confidence: 99%
“…Other recovery studies after oxidant injury (Welsh et al, 1985;Rochat et al, 1993;Meyer et al, 2001) and after surfactant treatment (Pasternak and Miller, 1996) have been performed on MDCK cell monolayers. The severity of the insult resulting from increased exposure time (Welsh et al, 1985;Rochat et al, 1993;Pasternak and Miller, 1996;Meyer et al, 2001) and the agent of injury (Pasternak and Miller, 1996) were found to be important factors in the ability of the BF to recover. Although the ability of KGF to protect against oxidant-induced permeability has been well documented (Mason et al, 1996;Yi et al, 1996;Waters et al, 1997;Savla and Waters, 1998;Gillis et al, 1999), no previous attempts have been made to determine whether KGF's influence extends to repair of the barrier after it had been compromised.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between the tight junction proteins and the actin cytoskeleton appears to be important for the maintenance of barrier function during exposure to ROS. ROS-induced increases in albumin and manitol permeability (Rochat et al, 1993;Waters et al, 1997) and conductance (Welsh et al, 1985;Yamaya et al, 1995) and decreases in TER (Chapman et al, 2002) were accompanied by altered actin cytoskeleton structure (Welsh et al, 1985;Waters et al, 1997;Chapman et al, 2002). In intestinal epithelial cells, ROS-induced barrier dysfunction was correlated with a decrease in the amount of actin associated with the cytoskeleton (Banan et al, 2000).…”
mentioning
confidence: 99%